Effect of Parecoxib and transversus abdominis plane block on postoperative anxiety and cognition: A randomized controlled-trial - Zhang, Fuzhen; Wang, Chengzhi; Li, Kan; Cheng, Xingyuan; Meng, Chenxue; Kang, Rongtian (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate the impact of parecoxib and transversus abdominis plane block on postoperative anxiety and early cognitive function in patients undergoing laparoscopic intestinal surgery. Method: The multicentre, randomised controlled trial was conducted at three tertiary hospitals in China from September 1, 2020, to September 30, 2022, and comprised individuals aged 60-85 years scheduled for elective laparoscopic intestinal surgery They were randomised into 4 groups. Patients in group C received normal saline. Patients in group P were given parecoxib 40mg intravenously 30 minutes before the start of surgery and 10 minutes after the end of surgery. In group T, a bilateral transversus abdominis plane block was performed 30 minutes before the start of surgery. Patients in group PT received a combination of interventions used in groups P and T. Serum samples of all the patients were obtained one day before surgery, 30 minutes after surgery and 24 hours after surgery. Anxiety levels were assessed one day before surgery, 24 hours after surgery, and 7 days after surgery. Data was analysed using SPSS 25. Results: Of the 205 patients, 115(56%) were males and 90(44%) were females. There were 51(24.9%) patients in group C with mean age 67.61±5.46 years, 51(24.9%) in group P with mean age 66.53±4.30 years, 52(25.3%) in group T with mean age 67.23±5.36 years and 51(24.9%) in group PT with mean age 66.49±4.62 years. Compared to group C, anxiety scores in groups P and PT were significantly lower at 24 hours post-surgery (p<0.05). Compared to group C, the concentration of tumour necrosis factor-alpha in the serum samples of groups P and group PT was significantly lower at 30 minutes after surgery (p< 0.05). Conclusion: A single transversus abdominis plane block did not have a significant effect on postoperative anxiety and cognition, while parecoxib could alleviate postoperative anxiety in elderly patients undergoing laparoscopic intestinal surgery. RCT Reg No: ChiCTR1900024953. Key Words: Anti-inflammatory agents, Non-steroidal, Anxiety, Cognition.